Analisis Kompetensi Agen Asuransi Kasus Bumi Putera Syariah Palembang - Sahirrudin Sahirrudin; Maya Panorama; Listiawati Listiawati (JES (Jurnal Ekonomi Syariah), 2018)
The success of a company needs employees who are competent, experienced and strong. Islamic insurance companies certainly require employees who have knowledge about insurance in accordance with Islamic sharia principles. In the case of the Islamic insurance company Bumi Putera Palembang in 2015 to 2016 there are 40 insurance policyholders who worked in a government agency to terminate the employment relationship between the insurance and policyholders. This is because there is no transparency related to monthly installment payments that should be proven by a deposit or proof of receipt of payment in full by the field agent to the policy holder. This is not in line with the principles of Islamic insurance, namely avoiding the elements of gharar, maysir and usury. Islam emphasizes aspects of justice, likes and likes and togetherness faces risks in every effort and investment pioneered. This aspect is the concept offer to replace gharar, maysir and riba that have been happening in conventional institutions. The focus of research is on the competency of agents (wakalah) in the sharia Islamic Bumi Putera insurance company in the city of Palembang. The result is obtained from the conclusions of six indicators and evidenced by the table of productive reports of agents related to product marketing that human resources in agents /wakalah Bumi Putera Syariah Life Insurance have not described competency and professionalism. This can be seen from the lack of insurance products sold, attitudes to field issues and the achievement of the target customers determined by the company. Keywords: Insurance Agent Competency, Bumi Putera Syariah